INTERACT-NET: An Interactive Interface for Multimedia Machine Learning - Kopiler, Alberto; Novello, Tiago; Schardong, Guilherme; Schirmer, Luiz; Perazzo, Daniel; Velho, Luiz (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2024)
INTERACT-NET is a study of interactive human-computer interfaces for use in pipelines of multimedia using ma-chine learning (ML), image processing, and computer graphics.